Geomorphology of marine and glacio-lacustrine terraces and raised shorelines in the northern sector of Península Brunswick, Patagonia, Straits of Magellan, Chile. Issue 2 (13th November 2018) - De Muro, Sandro; Tecchiato, Sira; Porta, Marco; Buosi, Carla; Ibba, Angelo
ABSTRACT: This paper illustrates a detailed geomorphological map (scale 1:50, 000) of the marine and transitional terraces (glacio-lacustrine to marine) and raised shorelines linked to Holocene glacio-eustasy and neo-tectonics in the northern area of the Brunswick Penìnsula (Chilean region of the Strait of Magellan). The mapped area is located in Tierra del Fuego between the Segunda Angostura and Seno Otway. This map is the result of geomorphological field survey data integrated with the interpretation of aerial photographs and remote sensing imagery. The survey has allowed the mapping of a sequence of terraces and raised shorelines to be completed. The sequence mainly consists of four orders of marine and glacio-lacustrine terraced deposits, with elevations ranging from 25 to 1 m above mean sea level. The map also presents other landforms and deposits, with their formation linked to littoral, fluvial, glacial and aeolian processes.